(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
In the scientific article, the level of toxicity and danger caused by the chronic effect of various percentage solutions of sodium fluoride on the body of white mice for 3 months was determined. Accordingly, from the analysis of the data obtained from the experiments, it was determined that sodium fluoride is a substance with high toxicity to the organism of white mice.